Effect of reperfusion injury from distant ischemia to small intestine (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND The ileum is the most vulnerable part of the small intestine that plays an important role as the motor of multisystem organ failure. Villous damage is demonstrated after ligation of supply artery in mice; however, there is no study on the ileum after distant ischemic organs. Thus, this study was aimed to find out ileal villous changes following reperfusion injury, the protective effects of ischemic hypothermia and ischemic preconditioning. METHODS An experimental study conducted enrolled 21 subjects of Oryctolagus cuniculus. Ischemia is induced by ligation of the femoral artery for 4 hours. Eight hours after ligation was released, ileum and duodenal specimens were taken through laparotomy. H&E stained specimens were examined for histomorphological changes. Villi change scores, tissue level of hypoxia-inducible factor-1α (HIF-1α), malondialdehyde (MDA), and occludin were statistically analyzed in four treatment groups, namely ischemia, ischemic hypothermia, ischemic preconditioning, and control. RESULTS Intestinal villi changes were found following ischemic-induced arterial ligation. Ileal villi changes showed differences with the duodenum and controls as indicated by the villi damage scores, increased tissue HIF-1α and MDA, and decreased occludin levels. Ileal villi changes in the ischemic and ischemic hypothermia groups showed significant changes with controls; whereas the ischemic preconditioning group showed no significant differences. CONCLUSIONS Ischemia at a distance leads to both histomorphological and biochemical damage of the ileal villi and disrupts the integrity of the intestinal mucosal barrier. In addition, the study showed a protective effect of ischemic preconditioning.